Prevalence and factors associated to depression among geriatric population in a rural area of Kanyakumari district Tamil Nadu - John, Jossy; Nath, Kasturi R. (International Journal Of Community Medicine And Public Health, 2019)
Background: Aging is a universal process. It has been documented that elderly are more prone to psychological problems and depression is the commonest geriatric psychiatric disorder. In India the prevalence of depression among elderly population between 13% and 25%. Depression usually becomes unnoticed and untreated in the elderly. Depression in late life is associated with significant morbidity including deficits in a range of cognitive functions, functional impairment, decreased quality of life, increased rate of suicide. The objectives of this study was to find out the prevalence of depression and its risk factors in geriatric population. Methods: This cross-sectional study was conducted from March 2017 to August 2017 among 75 elderly people who were attending the rural health centre Marappadi were included for the study. Depression was assessed by Geriatric Depression Scale (GDS). Results: The mean age of the participants were 72.63. Majority of them were females (56%). Most of them had middle school education (48 %) and 77.3% belong to joint family. The overall prevalence of depression in the study population was 76%. 30.7% of the elderly had severe depression and 16% are having moderate depression. There is significant association between depression with female sex, primary education, marital status, lower socio-economic status and presence of chronic illness. Conclusions: This study indicates high prevalence of depression in elderly population. Female sex, unemployment, marital status as married and joint family are the risk factors of depression in geriatric population.